2002
DOI: 10.1143/jjap.41.5809
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bond and Crystal Deformation of Cellulose in Sub/Super-critical Water

Abstract: A reflection objective-employed collinear thermal lens microscope (roco-TLM) is developed in which a reflection objective lens is used for collinearly focusing, in a mode-mismatched configuration, both an excitation laser beam at 260 nm and a probe laser beam at 632 nm. With the microscope, unsymmetrical distortions of a thermal lens image obtained with a reflection objective were reduced. The cause of the diffraction pattern in a thermal lens image observed with the roco-TLM is discussed as well. #

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Experimental evidence exists for this from Sasaki et al (2004) as discussed below. Further, Ito et al (2002) found that the population of hydrogen bonds between cellulose chains decreases with increasing water density. This would support our observation that increasing water density above a certain density value causes the dissolution temperatures to increase.…”
Section: Discussion On Dissolution Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental evidence exists for this from Sasaki et al (2004) as discussed below. Further, Ito et al (2002) found that the population of hydrogen bonds between cellulose chains decreases with increasing water density. This would support our observation that increasing water density above a certain density value causes the dissolution temperatures to increase.…”
Section: Discussion On Dissolution Processesmentioning
confidence: 99%
“…In simulations, Ito et al (2002) studied small (54 glucose units) arrangements of monoclinic crystalline cellulose of Ib phase in subcritical and SCW at densities of 310, 880, and 1000 kg/m 3 . Those authors found that the population of hydrogen bonds between cellulose chains decreases to half as the temperature increases from room temperature to about 475°C.…”
Section: Discussion On Dissolution Processesmentioning
confidence: 99%
“…Water evaporated more readily from the NCC/ water solution than from the Res.-CBD-NCC/water solution. This finding is somewhat surprising due to the strong hydrogen bonds between NCC hydroxyl groups and the water molecules (Ito et al 2002). At the same time, the specific binding of Res.-CBD to NCC, as well as its chemical bonding with epoxide groups at the droplet interface, may be the base of the slower rate of evaporation.…”
Section: Resultsmentioning
confidence: 99%
“…It implies that cellulose I␣ occupied more proportion in the residue of waste paper sample 5 which crystallinity was lower than the other samples'. The crystalline allomorphs structure of cellulose I␤ was more stable than that of cellulose I␣ (Ito et al, 2002). The relative content of cellulose I␤ was higher in sample 1 with high crystallinity and this improved the stability of cellulose structure.…”
Section: Mircostructure Changes Of Waste Paper Fiber After Conversionmentioning
confidence: 90%
“…As is shown in the some research works, the crystallinity of cellulose is increased during the recycle process (Chen, Wang, Wan, & Ma, 2010), the fibrils appear to aggregate and form a more compact structure when the hemicellulose is removed, which led to the inaccessibility of fiber for reaction (Wan, Wang, & Xiao, 2010). The distorted cellulose and small initial amount of cellulose I␣ were converted to cellulose I␤ (Hult, Iversen, & Sugiyama, 2003) which is more stable in the cellulose crystalline allomorphs (Ito, Hirata, Sawa, & Shirakawa, 2002). If we can evaluate the cellulose supramolecular changes and the further effect on the conversion property of waste paper in HCW, it will help to create a way to improve the waste paper conversion efficiency in HCW.…”
Section: Introductionmentioning
confidence: 99%